Lithium-titanium composite oxide comprising primary particles coated with aluminum, and method for preparing same
By applying aluminum to the primary particles of lithium titanium composite oxide, the safety hazards of lithium titanate oxide under high-speed charging and discharge and low temperature conditions are solved, and the high-temperature stability and safety of the battery are improved.
Patent Information
- Application Number
- CN202510084493.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2018-03-12
- Filing Date
- 2019-03-12
- Publication Date
- 2025-04-25
AI Technical Summary
The lithium titanate oxide used in existing lithium secondary batteries has safety hazards under high-speed charging and discharge and low temperature conditions, mainly due to the reaction of titanium and electrolyte to produce gas, and the high residual lithium amount leads to a decrease in high temperature safety.
By applying aluminum to the primary particles of the lithium-titanium composite oxide, lithium-titanium composite oxide containing primary particles of aluminum is formed, thereby reducing the electrolyte decomposition caused by residual lithium and titanium ions in the battery, thereby inhibiting gas generation.
It effectively reduces the amount of gas generated in the battery, improves the high temperature stability and safety of the battery, and improves the electrochemical characteristics.
Smart Images

Figure CN119873883A_ABST
Abstract
Description
[0001] This application is a divisional application of a patent application with application number 201980019243.0, application date March 12, 2019, and invention name “Lithium-titanium composite oxide comprising primary particles coated with aluminum and preparation method thereof”. Technical Field
[0002] The present invention relates to a lithium titanium composite oxide comprising primary particles coated with aluminum and a method for preparing the same. Background Art
[0003] Depending on the application of the battery, various properties are required for non-aqueous electrolyte batteries. For example, when a non-aqueous electrolyte battery is used in a digital camera, it is expected to be discharged at a current of about 3C (Coulomb), while when it is used in a hybrid vehicle, it is expected to be discharged at a current of at least about 10C. In view of such a situation, non-aqueous electrolyte batteries used in the above-exemplified technical fields are particularly required to have high current properties.
[0004] Most of the lithium secondary batteries currently in common use use carbon materials as cathode materials. Although carbon has the advantages of excellent conductivity and high capacity, it is difficult to apply to automobiles that put safety first due to poor thermal stability, low interchangeability with electrolytes, and easy formation of dendrites on the electrode surface. Therefore, there are many studies on using lithium titanate oxide (LTO) as a cathode material to replace carbon. Lithium titanate oxide has almost no volume change during charge and discharge, so it has good structural stability. Due to the relatively high potential of 1.5V (vs Li+ / Li), it does not form dendrites even if overcharged, and there is no safety problem such as decomposition of electrolytes, so it has favorable properties under high-speed and low-temperature working conditions.
[0005] Although lithium titanate oxide (Li4Ti5O 12 , LTO) material has the disadvantages of high working voltage compared to carbon cathode materials with working voltage of 1.3-1.6V and low reversible capacity of 170mAh / g, but it has the advantages of high-speed charge and discharge, almost no irreversible reaction (initial efficiency of more than 95%), low reaction heat and excellent safety. In addition, the theoretical density of carbon materials is as low as about 2g / cm 3 , while Li4Ti5O 12 Although the theoretical density is as high as 3.5g / cm 3 , but the capacity of the same volume is at a similar level to that of carbon substances.
[0006] Such preparation methods of lithium titanate oxide include, for example, a solid phase method, a quasi-solid phase method and a sol-gel method. Among them, the quasi-solid phase method is a method for preparing lithium titanate oxide by mixing solid reaction raw materials and then slurrying them, which includes many steps such as drying, first crushing, heat treatment and second crushing. The preparation process is complicated. If the steps of each process cannot be properly controlled, it is difficult to prepare lithium titanate oxide with the desired physical properties. It has the disadvantage that it is not easy to remove impurities from the lithium titanate oxide.
[0007] Among them, LiOH and / or Li2CO3 are used as the above-mentioned lithium compound. When the above-mentioned lithium compound is used, there is a problem that the amount of residual lithium existing on the surface of the anode active material in the form of LiOH and Li2CO3 is high.
[0008] Such residual lithium, that is, unreacted LiOH and Li2CO3 react with the electrolyte in the battery to induce gas generation and swelling, which will cause a serious decrease in high temperature safety.
[0009] Furthermore, it has recently been discovered that titanium in lithium titanate oxide reacts with an electrolyte to generate gas in the following manner.
[0010] Summary of the invention
[0011] Technical issues
[0012] An object of the present invention is to solve the above-mentioned conventional problems and to provide a lithium-titanium composite oxide having a novel structure and including primary particles coated with aluminum, wherein the generation of gas can be effectively regulated by coating the primary particles of the lithium-titanium composite oxide with a bimetal.
[0013] Another object of the present invention is to provide a method for producing the lithium-titanium composite oxide comprising primary particles coated with aluminum according to the present invention.
[0014] Solution
[0015] The present invention aims to solve the above-mentioned problems and provides a lithium-titanium composite oxide comprising primary particles coated with aluminum.
[0016] The lithium titanium composite oxide of the present invention is characterized in that the lithium titanium composite oxide is a secondary particle formed by agglomeration of a plurality of primary particles, and the size of the secondary particle is 7 μm to 20 μm.
[0017] The lithium-titanium composite oxide of the present invention is characterized in that the residual lithium content of the lithium-titanium composite oxide is 2000 ppm or less.
[0018] The residual lithium in the battery, that is, the gas generation and swelling caused by the reaction of unreacted LiOH and Li2CO3 with the electrolyte, etc., can cause a serious decrease in high temperature safety. However, the lithium-titanium composite oxide containing primary particles coated with aluminum of the present invention reduces the residual lithium in the battery and reduces the amount of gas generated in the battery, thereby improving the high temperature stability of the battery (see Table 11 of the present application).
[0019] The lithium titanium composite oxide of the present invention is characterized in that the intensity of the rutile titanium dioxide peak is within 3% of the lithium titanate oxide base peak, and the intensity of the anatase titanium dioxide peak is within 1% of the lithium titanate oxide base peak.
[0020] The lithium titanium composite oxide of the present invention is characterized in that the particle size distribution of the lithium titanium composite oxide changes with application of ultrasonic waves.
[0021] The lithium-titanium composite oxide of the present invention is characterized in that the secondary particles of the lithium-titanium composite oxide become primary particles when producing an electrode.
[0022] According to an experimental example of the present invention, in order to analyze the particle size of the lithium titanium composite oxide containing primary particles coated with aluminum of the present invention, ultrasonic waves are applied to confirm the change in particle size when ultrasonic waves are applied or not, and it can be confirmed that the particle size after ultrasonic waves are applied is smaller than the particle size before ultrasonic waves are applied. As a result, when the lithium titanium composite oxide of the present invention is used to prepare an electrode, the lithium titanium composite oxide changes to a primary particle form that is not a secondary particle form, thereby improving the electrochemical characteristics of the battery (refer to Figure 7 ).
[0023] Furthermore, the present invention provides an electrode for a lithium secondary battery comprising the lithium-titanium composite oxide of the present invention.
[0024] The electrode for a lithium secondary battery comprising a lithium titanium composite oxide of the present invention is characterized by comprising primary particles having a D50 of 1.0 μm to 4.0 μm obtained by pulverizing secondary particles of the lithium titanium composite oxide.
[0025] In addition, the present invention also provides a method for preparing a lithium-titanium composite oxide containing primary particles coated with aluminum, comprising: step i), solid-phase mixing a lithium-containing compound, a titanium oxide, and a heterogeneous metal compound in a stoichiometric ratio; step ii), dispersing the solid-phase mixture of the above step i) in a solvent and wet-crushing it until it contains particles with an average particle size of 0.1 μm to 0.2 μm to prepare a slurry; step iii), spray-drying the above slurry to form particles; step iv), calcining the above spray-dried particles; step v), crushing the above calcined particles; step vi), dispersing the mixture of the above crushed particles and the aluminum compound in a solvent and stirring it to prepare a slurry; step vii), spray drying; and step viii), heat treatment.
[0026] The method for producing a lithium-titanium composite oxide comprising primary particles coated with aluminum of the present invention is characterized in that the dissimilar metal compound is a zirconium compound.
[0027] The method for producing a lithium-titanium composite oxide comprising primary particles coated with aluminum of the present invention is characterized in that the aluminum compound is aluminum sulfate.
[0028] The method for producing a lithium titanium composite oxide comprising primary particles coated with aluminum of the present invention is characterized in that in the calcining step, heat treatment is performed at a temperature of 700° C. to 800° C. for 10 to 20 hours.
[0029] The method for producing a lithium titanium composite oxide comprising primary particles coated with aluminum of the present invention is characterized in that in the heat treatment step, the heat treatment is performed at a temperature of 400° C. to 500° C. for 10 to 20 hours.
[0030] Effects of the Invention
[0031] The lithium-titanium composite oxide of the present invention comprising primary particles coated with aluminum is crushed again after the preparation of the lithium-titanium composite oxide, and the crushed particles are mixed with an aluminum compound and then spray-dried. Since the crushed primary particles are coated with aluminum, the battery comprising the lithium-titanium composite oxide of the present invention comprising primary particles coated with aluminum shows the effect of inhibiting the decomposition of the electrolyte caused by titanium ions of the existing lithium-titanium composite oxide and the generation of gas due to residual lithium. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 The results of the measurement of the change in particle size with wet pulverization time are shown.
[0033] Figure 2 The results of scanning electron microscope (SEM) images of the lithium-titanium composite oxide before calcination are shown.
[0034] Figure 3The results of scanning electron micrographs of the calcined lithium-titanium composite oxide are shown.
[0035] Figure 4 The results of scanning electron micrographs of the cross-section of the calcined lithium-titanium composite oxide are shown.
[0036] Figure 5 The results of scanning electron micrographs of the calcined and crushed lithium-titanium composite oxide are shown.
[0037] Figure 6 A scanning electron microscope photograph of an electrode prepared from the lithium-titanium composite oxide of the present invention is shown.
[0038] Figure 7 The results of detecting changes in particles of a lithium-titanium composite oxide prepared in an experimental example of the present invention after calcination depending on whether or not ultrasonic waves were applied are shown.
[0039] Figure 8 A scanning electron microscope photograph of the lithium-titanium composite oxide particles of the present invention is shown. DETAILED DESCRIPTION
[0040] The present invention is described in more detail below by way of examples, but the present invention is not limited to the following examples.
[0041] Example 1. Preparation of lithium titanium composite oxide
[0042] As starting materials, 1 mol of lithium carbonate, 1 mol of anatase titanium oxide and 1 mol of zirconium hydroxide were solid-phase mixed and stirred in water to dissolve them. Next, zirconium oxide microbeads were wet-milled at a rotation speed of 3000 rpm, spray-dried under the conditions of a hot air temperature of 250°C and an exhaust hot air temperature of 110°C, and heat-treated in an air atmosphere at 700-800°C for 10-20 hours to prepare a lithium-titanium composite oxide doped with zirconium (Zr) as a bimetallic.
[0043] Experimental example: Particle size measurement based on wet grinding time
[0044] The zirconium oxide microbead particles used in the wet grinding in Example 1 and the slurry particle size according to the wet grinding time were tested. The results are as follows: Figure 1 shown.
[0045] The zirconium and the wet pulverization time were adjusted to prepare slurries with different particle sizes. The particle sizes of the prepared slurries and the particle size distribution of secondary particles prepared using the slurries were measured. The results are shown in Table 1 below.
[0046] Table 1
[0047]
[0048] In the above Example 1, the scanning electron microscope images of the lithium titanium composite oxide before calcination and the lithium titanium composite oxide after calcination were taken as follows: Figure 2 and Figure 3 shown.
[0049] The results of testing the particle size of the slurry prepared in Example 1 and its relationship with the primary particle size of the active material prepared therefrom are shown in Tables 2 and Figure 4 shown.
[0050] exist Figures 2 to 4 As shown in Table 2, the influence of the slurry particle size on the shape and size of the primary particles in the secondary particles before calcination and the primary particles in the secondary particles after calcination can be confirmed.
[0051] Table 2
[0052] distinguish SPL-1 SPL-2 SPL-3 SPL-4 SPL-5 Slurry particle size 0.54 0.39 0.30 0.22 0.10 Primary particle size 0.55 0.47 0.35 0.23 0.12
[0053] Experimental example: particle cross-section scanning electron microscope detection
[0054] The results of the scanning electron microscope examination of the cross section of the calcined lithium titanium composite oxide prepared in Example 1 are as follows: Figure 4 shown.
[0055] exist Figure 5 It can be seen that the primary particle size of SPL-1 with a slurry particle size of 0.1 is minimized and uniformly mixed compared to SPL-1 with a slurry particle size of 0.54. Therefore, during the heat treatment, pores generated as carbon dioxide is discharged are formed very uniformly.
[0056] Example 2. Crushing into primary particles
[0057] The lithium-titanium composite oxides of SP-1 to SP-5 prepared in Example 1 were pulverized.
[0058] The particle size distribution of particles of SP-1 to SP-5 was measured after pulverizing the particles, and the results are shown in Table 3 below.
[0059] Table 3
[0060]
[0061]
[0062] The results of scanning electron microscopy of the crushed particles are as follows: Figure 6 shown.
[0063] Example 3. Preparation of lithium titanium composite oxide with primary particles coated with aluminum
[0064] Aluminum sulfate as an aluminum compound was mixed with the slurry pulverized in Example 2, and water was mixed as a solvent, followed by stirring to coat the primary particles with aluminum.
[0065] The particles were spray dried at a hot air temperature of 250°C and an exhaust hot air temperature of 110°C, agglomerated into secondary particles again, and heat treated at 450°C in an air atmosphere for 10 hours to prepare a lithium-titanium composite oxide whose primary particles were surface-treated with aluminum.
[0066] Experimental Example: Confirmation of physical properties according to aluminum coating content
[0067] The physical properties of the aluminum sulfate added in Example 3 were examined according to the coating content. The results are shown in Table 4 below.
[0068] Table 4
[0069]
[0070] Example 4
[0071] Particles were prepared and their physical properties were measured in the same manner as in Example 3 except that the heat treatment temperature was adjusted to 450°C. The results are shown in Table 5 below.
[0072] Table 5
[0073]
[0074] Experimental example
[0075] Particles were prepared and their physical properties were measured in the same manner as in Example 3 except that the heat treatment temperature was adjusted to 475°C. The results are shown in Table 6 below.
[0076] Table 6
[0077]
[0078]
[0079] Experimental example: Physical property testing according to heat treatment temperature
[0080] Particles were prepared and their physical properties were measured in the same manner as in Example 3 except that the heat treatment temperature was adjusted to 500°C. The results are shown in Table 7 below.
[0081] Table 7
[0082]
[0083] Experimental example: Physical property testing according to heat treatment temperature
[0084] Particles were prepared and their physical properties were measured in the same manner as in Example 3 except that the heat treatment temperature was adjusted to 525°C. The results are shown in Table 8 below.
[0085] Table 8
[0086]
[0087]
[0088] Experimental example: Physical property testing according to heat treatment temperature
[0089] Particles were prepared and their physical properties were measured in the same manner as in Example 3 except that the heat treatment temperature was adjusted to 550°C. The results are shown in Table 9 below.
[0090] Table 9
[0091]
[0092] Experimental example: Physical property testing based on aluminum content
[0093] Experimental example: Gas generation detection
[0094] The lithium-titanium composite oxide containing primary particles coated with aluminum of the above embodiment was immersed in 4 ml of electrolyte (PC / EMC / DMC=2 / 2 / 6, LiPF6=1.0M) and stored at 80°C for 2 weeks. The gas generation was then analyzed. The results are shown in Table 10 below.
[0095] Table 10
[0096]
[0097] Preparation Example. Electrode Preparation
[0098] The lithium-titanium composite oxide prepared in the above embodiment is used as the anode active material, a lithium foil is used as the relative electrode, a porous polyethylene film (manufactured by Celgard LLC., model: Celgard 2300, thickness: 25 μm) is used as a separator, and a liquid electrolyte in which 1 mol of LiPF6 is dissolved in a solvent prepared by mixing ethylene carbonate and dimethyl carbonate in a volume ratio of 1:2 is used, and electrodes and coin-type batteries are prepared according to a known preparation process.
[0099] Experimental example: Scanning electron microscope image detection
[0100] The results of scanning electron microscopy of the prepared electrodes are shown in Figure 6 shown.
[0101] Experimental Example. Analysis of particle size change of lithium-titanium composite oxide with aluminum-coated primary particles
[0102] After calcining the lithium titanium composite oxide coated with aluminum as the primary particles prepared in the embodiment of the present invention, ultrasonic waves were applied to detect the particle changes depending on whether ultrasonic waves were applied. The results are as follows: Figure 7 As shown in Table 11.
[0103] Table 11
[0104]
[0105] Experimental example: Electrochemical characteristics detection
[0106] The electrochemical characteristics of the battery containing the particles prepared in the above examples were tested, and the results are shown in Table 12 below.
[0107] Table 12
[0108]
[0109]
Claims
1. A lithium-titanium composite oxide, characterized in that It comprises primary particles coated with aluminum.
2. The lithium-titanium composite oxide according to claim 1, characterized in that The lithium-titanium composite oxide is a secondary particle formed by agglomeration of a plurality of primary particles, and the size of the secondary particle is 7 μm to 20 μm.
3. The lithium-titanium composite oxide according to claim 1, characterized in that The residual lithium content of the lithium-titanium composite oxide is 2000 ppm or less.
4. The lithium-titanium composite oxide according to claim 1, characterized in that The intensity of the rutile titanium dioxide peak of the lithium titanium composite oxide is within 3% of the base peak of the lithium titanate oxide.
5. The lithium-titanium composite oxide according to claim 1, characterized in that The intensity of the anatase-type titanium dioxide peak of the lithium titanium composite oxide is within 1% of the base peak of the lithium titanate oxide.
6. The lithium-titanium composite oxide according to claim 1, characterized in that The particle size distribution of the lithium-titanium composite oxide changes with the application of ultrasonic waves.
7. The lithium-titanium composite oxide according to claim 1, characterized in that The lithium-titanium composite oxide secondary particles become primary particles when preparing an electrode.
8. An electrode, characterized in that: For use in a lithium secondary battery, the electrode comprises the lithium-titanium composite oxide according to any one of claims 1 to 7.
9. The electrode according to claim 8, characterized in that The electrode includes primary particles having a D50 of 1.0 μm to 4.0 μm, which are obtained by crushing secondary particles of the lithium-titanium composite oxide.
10. A method for preparing a lithium-titanium composite oxide comprising primary particles coated with aluminum, characterized in that: include: Step i), solid-phase mixing the lithium-containing compound, titanium oxide, and heterogeneous metal compound in a stoichiometric ratio; Step ii), dispersing the solid phase mixture of step i) in a solvent and wet-grinding the mixture until it contains particles with an average particle size of 0.1 μm to 0.2 μm to prepare a slurry; Step iii), spray drying the slurry to form particles; Step iv), calcining the spray-dried particles; Step v), crushing the calcined particles; Step vi), dispersing the mixture of the crushed particles and the aluminum compound in a solvent and crushing the mixture to prepare a slurry; Step vii), spray drying; as well as Step viii), heat treatment.
11. The method for preparing a lithium-titanium composite oxide comprising primary particles coated with aluminum according to claim 10, characterized in that: The above-mentioned dissimilar metal compound is a zirconium compound.
12. The method for preparing a lithium-titanium composite oxide comprising primary particles coated with aluminum according to claim 10, characterized in that: The above-mentioned aluminum compound is aluminum sulfate.
13. The method for preparing a lithium-titanium composite oxide comprising primary particles coated with aluminum according to claim 10, characterized in that: In the above-mentioned calcining step, heat treatment is performed at a temperature of 700° C. to 800° C. for 10 hours to 20 hours.
14. The method for preparing a lithium-titanium composite oxide comprising primary particles coated with aluminum according to claim 10, characterized in that: In the above heat treatment step, the heat treatment is performed at a temperature of 400° C. to 500° C. for 10 hours to 20 hours.